2014
DOI: 10.1097/sla.0b013e318295feba
|View full text |Cite
|
Sign up to set email alerts
|

Saline Versus Plasma-Lyte A in Initial Resuscitation of Trauma Patients

Abstract: Compared with 0.9% NaCl, resuscitation of trauma patients with Plasma-Lyte A resulted in improved acid-base status and less hyperchloremia at 24 hours postinjury. Further studies are warranted to evaluate whether resuscitation with Plasma-Lyte A improves clinical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
159
3
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(175 citation statements)
references
References 24 publications
3
159
3
10
Order By: Relevance
“…Fifty-eight articles were excluded after full text review due to following reasons: included colloid or other solutions in one of the trial arms (n=32); reviews (n=10); trials conducted exclusively in EDs (n=4); not an RCT (n=5); involving healthy volunteers (n=3), RCT in pediatric patients (n=2), RCT in a nonhuman setting (n=1) and article retracted (n=1). Finally, 11 RCTs (2,703 participants) were included in the final analysis ( Figure 1) (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). The composition of the balanced solutions tested in each RCT is shown in Table S2.…”
Section: Search Resultsmentioning
confidence: 99%
“…Fifty-eight articles were excluded after full text review due to following reasons: included colloid or other solutions in one of the trial arms (n=32); reviews (n=10); trials conducted exclusively in EDs (n=4); not an RCT (n=5); involving healthy volunteers (n=3), RCT in pediatric patients (n=2), RCT in a nonhuman setting (n=1) and article retracted (n=1). Finally, 11 RCTs (2,703 participants) were included in the final analysis ( Figure 1) (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22). The composition of the balanced solutions tested in each RCT is shown in Table S2.…”
Section: Search Resultsmentioning
confidence: 99%
“…Indeed, several clinical trials, even designed as prospective and randomized studies [54,55], had been conducted aimed at comparing several physiological effects of the two categories of intravenous solutions, whereas the scientific community still needed an understanding of whether such physiological effects (i.e. on acid-base equilibrium, on renal function and other organs) translated into a survival difference (Table 4).…”
Section: Clinical Evidencementioning
confidence: 99%
“…In experimental studies NS was found to cause electrolyte disturbances (hypernatraemia, hyperchloraemia) and metabolic acidosis (due to SID of 0 mEq/L), with its clinical sequelae of impaired kidney function, coagulation abnormalities, and inflammatory response [11]. Plasma-Lyte A as a calcium-free balanced crystalloid solution has been shown to produce lesser metabolic derangements in the population of trauma patients [12]. Zhou et al [13], in an experimental model of abdominal sepsis in rats, showed lesser metabolic acidosis and lower chloride concentration with Pasma-Lyte compared to NS.…”
Section: Discussionmentioning
confidence: 99%